The status of Cuvierina spoeli Rampal, 2002 and Cuvieria oryza Benson, 1835 (Gastropoda, Pteropoda, Cuvierinidae) - Janssen, Arie W. (Zootaxa, 2018)
The name Cuvierina spoeli Rampal, 2002 cannot be understood as a new replacement name (nom. nov.) for Cuvierina atlantica, as published in the unavailable name Cuvierina columnella (Rang, 1827) f. atlantica van der Spoel, 1970. The name atlantica was made available as a name of the species group in the combination Cuvierina columnella atlantica Bé, MacClintock & Currie, 1972, currently interpreted to represent the species Cuvierina atlantica. Cuvierina spoeli type material does not belong to C. atlantica, but to C. columnella of which it therefore is a junior subjective synonym. The name Cuvieria oryza Benson, 1835 was recognised to represent a senior synonym of Cuvierina urceolaris (Mörch, 1850), not a junior synonym or form of C. columnella Rang, 1827, as it was frequently interpreted by authors. The name C. oryza is here declared nomen oblitum and the name C. urceolaris, because in prevailing usage, is declared nomen protectum. The conditions of ICZN (1999, art. 23.9.1.1 and .2) are met.